EFEKTIVITAS PERMAINAN TRADISIONAL DALAM MENINGKATKAN SCHOOL ENGAGEMENT SISWA DI SDN 14 TELAGA BIRU - Rahmawaty Parman; Sri Astita Mohi; Putri Kireyna Demanto; Mutiara Kasim; Siti Agustina Mayaviranti; Novita Sari Mansyur; Sulistia Syah Buna (program studi psikologi, 2024)
School engagement is a number of psychological components that can be observed in the form of behaviour, such as the level of attendance, emotional involvement and the ability to identify emotions. Indicators that can be used as guidelines for school engagement behaviour are involvement in school, both academic and non-academic activities, the achievement of School Engagement is related to the stimulation provided. The stimulation provided in the form of traditional games carried out for generations has its own characteristics related to its aesthetics. Traditional games have excellent educational value that stimulates early childhood development, for children's motor development, trains children's social interaction with their friends, develops a person's character to enjoy learning various things. Traditional games must be cultivated by every generation. This study aims to determine whether there is an effect of the effectiveness of traditional games in increasing students' school engagement at SDN 14 Telaga Biru. The research used an experimental approach. The type of research design is One-Group Pretest-Posttest which is given treatment then measured again with a school engagement scale measuring instrument. The sample was 11 students, the sampling technique used in the study was nonprobability sampling, namely saturated sampling, often used when the population is less than 30 people. Data analysis using the Kolmogorov-Smirnov normality test, the result is the Asymp. Sig value of 0.027 is smaller than 0.05 so it can be concluded that the data from the tested variables are not normally distributed, then to see and test it using the non-parametric statistical test, the Wilcoxon test obtained a result of 0.008 <0.05, it can be concluded that the asym.sig of 0.008 is smaller than 0.05 which indicates that H1 is accepted or there is an effect and H0 is rejected.